Self‐reported and measured cardiorespiratory fitness similarly predict cardiovascular disease risk in young adults. Issue 6 (15th March 2012) - Ortega, F. B.; Sánchez‐López, M.; Solera‐Martínez, M.; Fernández‐Sánchez, A.; Sjöström, M.; Martínez‐Vizcaino, V.
<x xml:space="preserve">Abstract</x> We aimed to (a) examine the validity and reliability of the International FItness Scale (IFIS) in Spanish young adults and (b) compare the capacity of self‐reported vs measured fitness to predict cardiovascular disease (CVD) risk. The study comprised 276 participants (18–30 years). Fitness level (overall and specific components) was both self‐reported (IFIS) and measured using standard fitness tests. Total and trunk fat was assessed by dual‐energy X‐ray absorptiometry. We computed a previously validated metabolic syndrome score. A separate sample of 181 of same age and characteristics fulfilled IFIS twice for reliability purposes. The results of the present study support the validity and reliability of self‐reported fitness, as measured by IFIS, in Spanish young adults. Our data also suggest that not only measured cardiorespiratory fitness but also self‐reported cardiorespiratory fitness predicts CVD risk, as assessed by adiposity and metabolic syndrome indicators. The associations for muscular fitness (both reported and measured) differed depending on how it was expressed (i.e., absolute vs relative terms). Self‐reported fitness, as assessed by IFIS, can be a good alternative when physical fitness cannot be measured in large surveys.